The Application of the Qarshun 'Ajibun Media in Students' Understanding of the Nahwu (Grammar) Subject - Izzah, Nailul; Purnamasari, Nia Indah; Arifin, Ahmad; Paramita, Nurhapsari Pradnya; Munawar, Endang (Institut Agama Islam Negeri Curup, 2024)
This research aimed to enhance students' comprehension of the Nahwu subject, hoping to increase motivation and make Nahwu courses more enjoyable. With issues in mind, the difficulty of Ma'arif University Lampung students in understanding Nahwu courses was partly due to the absence of the pesantren education background of some students and the students' boredom with the course. The research method employed was qualitative field research. Data collection methods included observation, interviews, tests, and documentation. This research utilized a quasi-experimental design. Based on the test results, it was evident that the mean score of Group 1 in the initial or pretest was only 68.7, whereas Group 2 scored 77.7. After the learning process was conducted using the Magic Disc Arab Qarshun 'Ajibun media, the mean score of the experimental class (Group 1) reached 82.6, while the control class (Group 2) only reached 81.3. This indicated that the learning process using the Magic Disc Arab Qarshun 'Ajibun media could enhance students' learning comprehension and have a significant impact. Therefore, this media-based teaching method was a solution for delivering instructional material effectively, especially in the context of Nahwu. Additionally, this research provided a storyboard on the practical implementation of the Qarshun 'Ajibun Media to improve the understanding of Nahwu. For further research, it is recommended to carry out research & development studies on the Magic Disc Arabic Qarshun 'Ajibun media and can also apply the Magic Disc Arabic Qarshun 'Ajibun media as an exciting learning media to increase interest in learning Arabic and can increase anger Arabic, both from improving kalam (speaking) skills, kitabah (writing) skills and qiro'ah (writing) skills.